KEANEKARAGAMAN SERANGGA PADA PERTANAMAN KEDELAI (GLYCINE MAX L.) YANG DIAPLIKASI DAN TANPA APLIKASI INSEKTISIDA - Patrayasa, I Wayan; Toana, Moh. Hibban; Hasriyanty, Hasriyanty (AGROTEKBIS, 2018)
This study aimed to determine the diversity and the evenness ofinsects as well as the production of soybean plants (Glycine max L.) sprayed with and withoutinsecticide. This research was conducted in March to July 2016 and located in Sidera village, Sigi Biromaru  , Central Sulawesi province. The identification of the insects was done at the Plant Pests and Diseases Laboratory of Faculty of Agriculture of Tadulako University. The number of families and species of the insects was not affected by the insecticide sprayed but on their individual number.  The diversity of the insects under the soybean plantation both sprayed and un-sprayed was categorically moderate.  However, the spraying could increase the production up to 3 t/ha compared to the non-spraying which was only2.21 t/ha.